Comprehensive dental health care program at an orphanage in Nellore district of Andhra Pradesh - Dhanya Muralidharan; Nusrath Fareed; M Shanthi (Wolters Kluwer Medknow Publications, 2012)
Background: Provision of oral health care in India, especially for the underprivileged is limited due to inadequate finances and manpower. Resources of dental colleges in such a scenario can be utilized to provide prevention oriented oral health care. Aim: To improve the oral health status of children at an institute in Nellore district of Andhra Pradesh, India, through prevention based comprehensive dental health care program (CDHP). Design and Setting: A longitudinal institution based interventional study conducted among the primary grade children (n=162). Materials and Methods: Baseline data collection included (i) basic demographic data (ii) body mass index (BMI) (iii) assessment of the dentition status and treatment needs according to WHO 1997 criteria. The CDHP included group based dental health education, professional oral prophylaxis, weekly (0.2%) sodium fluoride mouth rinse program, biannual application of topical fluoride (1.23% APF), pit and fissure sealants for all first permanent molars and provision of all necessary curative services. Results: Mean treatment requirements per child decreased at 18 months. New caries lesions developed among four children. BMI of children with decay was seen to improve significantly after instituting the CDHP. Conclusion: CDHP is effective in overall improvement of general and oral health. In resource limited countries like India, such programs organized by dental schools can improve oral health.